2002
DOI: 10.1177/019394502762476988
|View full text |Cite
|
Sign up to set email alerts
|

Impairing Injuries among Medical Personnel

Abstract: Medically impairing injuries among medical personnel (n = 209) were analyzed based on data obtained from the Work-Related No-Fault Liability Insurance's (TFA) injury registration system. Almost half (98; 47%) were injured during patient care, of which 29 were injured as a result of physical trauma inflicted by the patient. When moving themselves between the homes of the patients and between different wards, 94 (45%) were injured (18 in vehicle crashes). The injuries most often resulting in medical impairment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A register-based study from Sweden found that paramedics had a higher rate of permanent medical impairment (2.2 per 1000 gainfully employed people per year) than other health service workers (mean 0.38 per 1000), but the incidence measured in paramedics was based on a small sample size of five [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A register-based study from Sweden found that paramedics had a higher rate of permanent medical impairment (2.2 per 1000 gainfully employed people per year) than other health service workers (mean 0.38 per 1000), but the incidence measured in paramedics was based on a small sample size of five [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy failed to identify a few studies included in a previous review, because no word for "ambulance workers" was identified in the databases citing these articles. It is also possible that we missed other studies comparing health status in different occupational groups where ambulance workers represent only one of many groups (e.g., data in only one row or column in the tables) [ 69 ], as in two of the studies known by the research group [ 8 , 9 ]. However, we believe it unlikely that this bias would change the overall conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, most studies examined the prevalence of post-traumatic stress disorder (PTSD; Bisson and Deahl, 1994; Moran and Britton, 1994; Van der Ploeg and Kleber, 2003) and the relevant coping strategies and predictors (Bennett et al, 2004; Brough, 2005; Marmar et al, 1999). After measures of mental health, studies then focused largely on physical health of ambulance workers (Öhman et al, 2002; Rodgers, 1998). The literature hence largely concentrates on evaluating ambulance personnel well-being in terms of negative outcomes such as job stress or illness.…”
mentioning
confidence: 99%
“…An important factor to consider when measuring self-perceived health status is the rate to which health problems influence one’s daily work. Research conducted by Ohman, Bylund, and Bjornstig (2002) concluded that, compared with the average population, Swedish AP were more limited in their physical activity when performing daily job functions (2.2‰ vs. 0.38‰; Ohman, Bylund, & Bjornstig, 2002). Work-related accidents among AP also may contribute to temporary or chronic health deterioration and occasionally to death (Gershon, Vlahov, Kelen, Conrad, & Murphy, 1995).…”
Section: Introductionmentioning
confidence: 99%